Studies on host invasion and mass production of Himalayan species of entomopathogenic nematodes - Vashisth, Sumit; Chandel, Y S; Chandel, R S (Indian Journal of Plant Protection, 2020)
ntomopathogenic nematodes (EPN) are highly effective biocontrol agents and have a broad host range infecting several species of insects belonging to different orders. To have an idea about infection mechanisms of EPNs, we compared oral and cuticular penetration ability of three species of Heterorhabditis taken from soils of Himachal Pradesh. These three strains were isolated from Sangla, Kamand and Rajgarh areas of Himachal Pradesh and named as Heterorhabditis spp. (HSG), Heterorhabditis spp. (HKM) and H. bacteriophora (HRJ), respectively. They showed limited oral penetration, but all of them had excellent cuticular penetration ability as observed in Achroia grisella. After 12 h post exposure, 71.2, 70.1 and 66.7 per cent of the infective juveniles (IJs) belonging to Heterorhabditis spp. (HSG), Heterorhabditis spp. (HKM) and H. bacteriophora (HRJ) penetrated through cuticle to reach the haemocoel and caused infection in A. grisella. Overall different isolates did not differ much in their ability to exploit different portals of entry into the larvae of A. grisella. Mass multiplication of Heterorhabditis spp. (HSG), Heterorhabditis spp. (HKM) and H. bacteriophora (HRJ) was done in vivo on three lepidopteran insects viz. Corcyra cephalonica, A. grisella and Bombyx mori which are highly susceptible to nematodes. For in vivo mass production of Heterorhabditis sp., C. cephalonica, A. grisella and B. mori were used. The average yield of IJs/larva was minimum (23020-26030) in C. cephalonica and maximum in B. mori (463080-546840) for differentÂ nematodes. For in vitro production, chicken offal medium was used. The yield was maximum for H. bacteriophora(HRJ) (17.70 x 106 IJs/flask).